Superhydrophobic ceramic oil-water separation membrane, preparation and application thereof

CN122912690APending Publication Date: 2026-10-16CHINA NAT PETROLEUM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510427526.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

专利文献CN106975369A公开一种用于油水分离的三氧化二铝陶瓷复合膜,采用氧化铝和粉煤灰为原料,利用丙烯酰胺或异丙烯酰胺为前驱体,经溶液共混制胚、陶瓷片烧结、水热处理和聚二甲基硅氧烷浸涂得到超疏水复合陶瓷膜;制备工艺复杂,成本高

Benefits of technology

[0024] (1) The superhydrophobic ceramic oil-water separation membrane provided by the present invention has excellent superhydrophobic properties and high oil-water separation efficiency; it has higher chemical stability and thermal stability; and it is suitable for various working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912690A_ABST
    Figure CN122912690A_ABST
Patent Text Reader

Abstract

The application discloses a super-hydrophobic ceramic oil-water separation membrane and a preparation method thereof. The method for preparing the super-hydrophobic ceramic oil-water separation membrane comprises the following steps: immersing surface-sulfhydrylated alumina porous ceramic pieces into a suspension liquid prepared by mixing alkyl-terminated polysiloxane, surface-sulfhydrylated mesoporous nanometer silicon dioxide, a photoinitiator and tetrahydrofuran, taking out after oscillation, and enabling the alkyl-terminated polysiloxane to be firmly fixed on the surface-sulfhydrylated mesoporous nanometer silicon dioxide and the surface-sulfhydrylated alumina porous ceramic surface through a sulfhydryl-alkene click chemical reaction under ultraviolet light irradiation, and the mesoporous silicon dioxide is firmly modified on the surface of the alumina porous ceramic pieces to obtain the super-hydrophobic ceramic oil-water separation membrane. The method has the advantages of mild reaction conditions, easily-obtained raw materials, low cost, simple operation, superior hydrophobic performance of the prepared super-hydrophobic ceramic oil-water separation membrane, high chemical stability and thermal stability, and high oil-water separation efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a superhydrophobic ceramic oil-water separation membrane, its preparation, and its application. Background Technology

[0002] With the continuous development of industries such as oil and gas, chemical metallurgy, transportation energy, food and pharmaceuticals, a large amount of oily wastewater is generated during industrial production and operation. This type of wastewater not only causes serious pollution to the natural environment but also has a detrimental impact on human life and health. Therefore, the advanced treatment and resource utilization of oily wastewater is not only an important issue for environmental protection but also a major requirement for sustainable industrial development. It is of great significance for alleviating water shortages, protecting the natural ecological environment, contributing to energy conservation and emission reduction, and achieving sustainable development goals. Traditional oil-water separation technologies suffer from low efficiency and high energy consumption, and may even introduce new pollutants, thus urgently requiring the development of new oil-water separation technologies. In recent years, advancements in materials science have greatly promoted technological progress in the field of oil-water separation. Membrane separation technology, with membrane materials as its core, is considered one of the most effective technologies for the advanced treatment of oily wastewater due to its high separation efficiency, low energy consumption, and strong adaptability.

[0003] With the development of surface superwetting control technology, special wettability enables membrane materials to absorb or repel liquids, separating complex oil-water mixtures and even oil-water emulsions, thus improving oil-water separation efficiency and showing promising application prospects. Ceramic materials possess excellent thermal stability, chemical stability, and antifouling properties, with long service life and easy cleaning. They can achieve oil-water separation even under harsh conditions, making them commonly used separation materials in the field of oil-water separation. However, the preparation and wettability control processes of most ceramic membrane materials are relatively complex, the synthesis process is cumbersome, and the stability of the special wettability layer on the surface is poor, making it easily worn away. This weakens or even eliminates the special wettability of the material surface, thereby significantly reducing the oil-water separation performance of the membrane material.

[0004] In the prior art, patent document CN103521095A discloses a tubular ceramic membrane for oil-water separation, which uses an alumina ceramic membrane tube as the substrate, coats the ceramic membrane with a membrane-forming solution containing polytetrafluoroethylene or polyvinylidene fluoride, and then prepares a hydrophobic and oleophilic ceramic membrane by sintering and drying. However, the separation performance of this tubular ceramic membrane for oil-water separation is limited, and it is suitable for oil-water separation systems with an oil content higher than 70%, but not suitable for separating oily wastewater with a high water content. Patent document CN106975369A discloses an alumina ceramic composite membrane for oil-water separation, which uses alumina and fly ash as raw materials, and acrylamide or isoacrylamide as precursors. The process involves solution blending to prepare the preform, sintering the ceramic sheet, hydrothermal treatment, and impregnation with polydimethylsiloxane to obtain a superhydrophobic composite ceramic membrane; however, the preparation process is complex and costly. Patent document 117865719A discloses a highly stable underwater superoleophobic silicon carbide ceramic film. The silicon carbide ceramic film is placed in a muffle furnace and oxidized and sintered at 500-900°C for 25-45 minutes, followed by plasma modification under a vacuum of 300-800 mT. The preparation and modification process is cumbersome, the synthesis conditions are complex, and the process controllability is low. Summary of the Invention

[0005] In view of the above problems, this invention is proposed to provide a superhydrophobic ceramic oil-water separation membrane and its preparation method to overcome or at least partially solve the above problems. The superhydrophobic ceramic oil-water separation membrane provided by this invention has excellent superhydrophobic properties, corrosion resistance and thermal stability, and high oil-water separation efficiency, and can be applied to oil-water separation conditions in various harsh environments.

[0006] As one aspect of the present invention, a method for preparing a superhydrophobic ceramic oil-water separation membrane is provided, comprising the following steps:

[0007] (1) Mix alkenyl-terminated polysiloxane, surface-thiolized mesoporous nano silica, photoinitiator and tetrahydrofuran to obtain a suspension;

[0008] The ratio of the volume of the alkenyl-terminated polysiloxane, the mass of the surface-thiolized mesoporous nano-silica, and the mass of the photoinitiator is 1 mL:(300-400) mg:1 mg.

[0009] (2) Immerse the surface-thiolized porous alumina ceramic sheet in the above suspension, shake, take it out, irradiate with ultraviolet light; wash, dry, and obtain a superhydrophobic ceramic oil-water separation membrane.

[0010] In a specific implementation, the alkenyl-terminated polysiloxane is one or any combination of vinyl-terminated polydimethylsiloxane, vinyl-terminated polyphenylsiloxane, and methacrylate-terminated dimethylsiloxane.

[0011] In a specific implementation, the photoinitiator is benzoin dimethyl ether.

[0012] In a specific implementation, in step (1), the volume ratio of the alkenyl-terminated polysiloxane to the tetrahydrofuran is (1-2):20.

[0013] In a specific implementation, in step (2), the oscillation time is 30-60 min and the ultraviolet light irradiation time is 20-40 min.

[0014] In a specific implementation, the method for preparing the surface-thiolized mesoporous nano-silica is as follows:

[0015] Mesoporous nano-silica was dispersed in an ethanol solution of a mercapto-modified surface modifier and refluxed at boiling for 5–12 h; then centrifuged, washed, and dried to obtain surface-mercapto-modified mesoporous nano-silica.

[0016] The concentration of the thiolated surface modifier in the ethanol solution of the thiolated surface modifier is 5-10 mg / mL, and the thiolated surface modifier is 3-mercaptopropyltriethoxysilane.

[0017] In a specific implementation, the mass ratio of the mesoporous nano-silica to the mercaptoized surface modifier is 1:(1-1.2).

[0018] In a specific implementation, the method for preparing the surface-thiolized porous alumina ceramic sheet is as follows:

[0019] Alumina porous ceramic sheets were immersed in an ethanol solution of a mercapto-modified surface modifier, shaken for 5–12 hours, and then removed; washed and dried to obtain surface-mercapto-modified alumina porous ceramic sheets.

[0020] The concentration of the thiolated surface modifier in the ethanol solution of the thiolated surface modifier is 5-10 mg / mL, and the thiolated surface modifier is 3-mercaptopropyltriethoxysilane.

[0021] As another aspect of the present invention, it relates to the superhydrophobic ceramic oil-water separation membrane prepared by the above method.

[0022] As another aspect of the present invention, it relates to the application of the above-mentioned superhydrophobic ceramic oil-water separation membrane in oil-water separation.

[0023] Compared with the prior art, the present invention has at least the following beneficial effects:

[0024] (1) The superhydrophobic ceramic oil-water separation membrane provided by the present invention has excellent superhydrophobic properties and high oil-water separation efficiency; it has higher chemical stability and thermal stability; and it is suitable for various working conditions.

[0025] (2) The method for preparing a superhydrophobic ceramic oil-water separation membrane provided by this invention involves an alkenyl-terminated polysiloxane reacting with thiol groups on the surface of mesoporous silica and the surface of porous alumina ceramic sheets under the action of ultraviolet light and a photoinitiator. This reaction forms carbon-sulfur bonds, allowing the alkenyl-terminated polysiloxane to be firmly covalently bonded to the surfaces of the mesoporous silica and porous alumina ceramic sheets. The mesoporous silica is then firmly modified onto the surface of the porous alumina ceramic sheets, resulting in a superhydrophobic ceramic oil-water separation membrane. This method has the advantages of high preparation efficiency, mild reaction conditions, and can be carried out in an air environment. The raw materials and substrates used are inexpensive, and the impregnation method is simple to operate. Attached Figure Description

[0026] Figure 1 This is a scanning electron microscope image of surface-thiolized mesoporous silica nanoparticles from Example 1;

[0027] Figure 2 This is a diagram showing the water contact angle of the superhydrophobic ceramic oil-water separation membrane in Example 1;

[0028] Figure 3 This is a scanning electron microscope image of the superhydrophobic ceramic oil-water separation membrane of Example 1;

[0029] Figure 4 This is a scanning electron microscope image of the superhydrophobic ceramic oil-water separation membrane of Example 4;

[0030] Figure 5 This is a scanning electron microscope image of the superhydrophobic ceramic oil-water separation membrane of Example 6. Detailed Implementation

[0031] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0032] In the embodiments and comparative examples of the present invention, the porous alumina ceramic sheet is circular with a diameter of 39 mm, a thickness of 3 mm, and an average pore size of 1 μm.

[0033] Example 1

[0034] This embodiment provides a method for preparing a superhydrophobic ceramic oil-water separation membrane, including the following steps:

[0035] 1) Thiolization modification of mesoporous nano silica surface: 0.5 g of 3-mercaptopropyltriethoxysilane (thiolization surface modifier, KH590) was dissolved in 100 mL of ethanol, and 0.5 g of mesoporous nano silica (particle size 100 nm) was added to it. The mixture was heated to boiling and refluxed for 5 h. The nanoparticles deposited at the bottom of the centrifuge tube were collected by centrifugation, washed 3 times with ethanol, and dried in a vacuum oven at 100 °C for 12 h to obtain surface-thiolized mesoporous nano silica.

[0036] 2) Cleaning of alumina ceramic sheet surface: Soak the porous alumina ceramic sheet in distilled water and ultrasonically clean it 3 times, then ultrasonically clean it 3 times with anhydrous ethanol, and dry it in a vacuum oven at 100℃ for 12 hours to obtain the cleaned porous alumina ceramic sheet.

[0037] 3) Surface thiolization modification of porous alumina ceramic sheets: 0.5 g of 3-mercaptopropyltriethoxysilane (thiolization surface modifier, KH590) was dissolved in 100 mL of anhydrous ethanol. The cleaned porous alumina ceramic sheets were immersed in the solution and shaken for 5 h. After shaking, the sheets were removed, washed three times with anhydrous ethanol, and dried in a vacuum oven at 100 °C for 5 h to obtain surface thiolized porous alumina ceramic sheets.

[0038] 4) Superhydrophobic modification of porous alumina ceramic sheets: 400 mg of surface-thiolized mesoporous nano-silica, 1 mL of vinyl-terminated polydimethylsiloxane (V-PDMS), 20 mL of anhydrous tetrahydrofuran, and 1 mg of benzoin dimethyl ether (photoinitiator, DMPA) were mixed to obtain a suspension; the surface-thiolized porous alumina ceramic sheets were immersed in the above suspension and shaken for 30 min before being removed; they were irradiated under ultraviolet light at a wavelength of 365 nm for 20 min; they were then ultrasonically cleaned three times alternately with anhydrous ethanol and dichloromethane, and dried in a vacuum oven at 60 °C for 12 h to obtain a superhydrophobic ceramic oil-water separation membrane.

[0039] The scanning electron microscope image of the surface-thiolized mesoporous silica nanoparticles obtained in test step (1) is shown below. Figure 1 .Depend on Figure 1 It is known that the surface-thiolized mesoporous nano-silica has a micromorphology with grooves on the surface. This type of hierarchical microstructure helps to improve the surface roughness of ceramic micro-nano composites and improve the hydrophobic properties of the material.

[0040] The water contact angle diagram of the superhydrophobic ceramic oil-water separation membrane prepared in this embodiment is shown below. Figure 2 As shown.

[0041] The microstructure of the superhydrophobic ceramic oil-water separation membrane prepared in this embodiment was tested, and the scanning electron microscope image is shown below. Figure 3 .Depend on Figure 3It is known that the surface of the superhydrophobic ceramic oil-water separation membrane has a micron / nano composite rough structure, which is beneficial to improving the hydrophobic properties of the ceramic membrane surface.

[0042] Example 2

[0043] This embodiment provides a method for preparing a superhydrophobic ceramic oil-water separation membrane, including the following steps:

[0044] 1) Thiolization modification of mesoporous nano silica surface: 0.6 g of 3-mercaptopropyltriethoxysilane (thiolization surface modifier, KH590) was dissolved in 100 mL of ethanol, and 0.5 g of mesoporous nano silica (particle size 100 nm) was added to it. The mixture was heated to boiling and refluxed for 5 h. The nanoparticles deposited at the bottom of the centrifuge tube were collected by centrifugation, washed 3 times with ethanol, and dried in a vacuum oven at 100 °C for 12 h to obtain surface-thiolized mesoporous nano silica.

[0045] 2) Cleaning of the alumina ceramic sheet surface: Same as step 2) in Example 1;

[0046] 3) Surface thiolization modification of porous alumina ceramic sheets: 1.0 g of 3-mercaptopropyltriethoxysilane (thiolization surface modifier, KH590) was dissolved in 100 mL of anhydrous ethanol. The cleaned porous alumina ceramic sheets were immersed in the solution and shaken for 5 h. After shaking, the sheets were removed, washed three times with anhydrous ethanol, and dried in a vacuum oven at 100 °C for 5 h to obtain surface thiolized porous alumina ceramic sheets.

[0047] 4) Superhydrophobic modification of porous alumina ceramic sheets: 400 mg of surface-thiolized mesoporous nano-silica, 1 mL of vinyl-terminated polydimethylsiloxane (V-PDMS), 20 mL of anhydrous tetrahydrofuran, and 1 mg of benzoin dimethyl ether (photoinitiator, DMPA) were mixed to obtain a suspension; the surface-thiolized porous alumina ceramic sheets were immersed in the above suspension and shaken for 30 min before being removed; they were irradiated under ultraviolet light at a wavelength of 365 nm for 20 min; they were then ultrasonically washed three times alternately with anhydrous ethanol and dichloromethane, and dried in a vacuum oven at 60 °C for 12 h to obtain a superhydrophobic ceramic oil-water separation membrane.

[0048] Example 3

[0049] This embodiment provides a method for preparing a superhydrophobic ceramic oil-water separation membrane, including the following steps:

[0050] 1) Thiolization modification of mesoporous nano silica surface: 1.0 g of 3-mercaptopropyltriethoxysilane (thiolization surface modifier, KH590) was dissolved in 100 mL of ethanol, and 1.0 g of mesoporous nano silica (particle size 100 nm) was added to it. The mixture was heated to boiling and refluxed for 5 h. The nanoparticles deposited at the bottom of the centrifuge tube were collected by centrifugation, washed 3 times with ethanol, and dried in a vacuum oven at 100 °C for 12 h to obtain surface-thiolized mesoporous nano silica.

[0051] 2) Cleaning of the alumina ceramic sheet surface: Same as step 2) in Example 1;

[0052] 3) Thiolization modification of porous alumina ceramic sheet surface: Same as step 3) in Example 1;

[0053] 4) Superhydrophobic modification of porous alumina ceramic sheets: 600 mg of surface-thiolized mesoporous nano-silica, 2 mL of vinyl-terminated polydimethylsiloxane (V-PDMS), 20 mL of anhydrous tetrahydrofuran, and 2 mg of benzoin dimethyl ether (photoinitiator, DMPA) were mixed to obtain a suspension; the surface-thiolized porous alumina ceramic sheets were immersed in the above suspension and shaken for 30 min before being removed; they were irradiated under ultraviolet light at a wavelength of 365 nm for 40 min; they were then ultrasonically cleaned three times alternately with anhydrous ethanol and dichloromethane, and dried in a vacuum oven at 60 °C for 12 h to obtain a superhydrophobic ceramic oil-water separation membrane.

[0054] Example 4

[0055] This embodiment provides a method for preparing a superhydrophobic ceramic oil-water separation membrane, including the following steps:

[0056] 1) Thiolization modification of mesoporous nano silica surface: 0.5 g of 3-mercaptopropyltriethoxysilane (thiolization surface modifier, KH590) was dissolved in 100 mL of ethanol, and 0.5 g of mesoporous nano silica (particle size 100 nm) was added to it. The mixture was heated to boiling and refluxed for 12 h. The nanoparticles deposited at the bottom of the centrifuge tube were collected by centrifugation, washed three times with ethanol, and dried in a vacuum oven at 100 °C for 12 h to obtain surface-thiolized mesoporous nano silica.

[0057] 2) Cleaning of the alumina ceramic sheet surface: Same as step 2) in Example 1;

[0058] 3) Surface thiolization modification of porous alumina ceramic sheets: 1.0 g of 3-mercaptopropyltriethoxysilane (thiolization surface modifier, KH590) was dissolved in 100 mL of anhydrous ethanol. The cleaned porous alumina ceramic sheets were immersed in the solution and shaken for 12 h. After shaking, the sheets were removed, washed three times with anhydrous ethanol, and dried in a vacuum oven at 100 °C for 5 h to obtain surface thiolized porous alumina ceramic sheets.

[0059] 4) Superhydrophobic modification of porous alumina ceramic sheet surface: 400 mg of surface-thiolized mesoporous nano-silica, 1 mL of vinyl-terminated polyphenylsiloxane (V-PMDMS), 20 mL of anhydrous tetrahydrofuran and 1 mg of benzoin dimethyl ether (photoinitiator, DMPA) were mixed to obtain a suspension; the surface-thiolized porous alumina ceramic sheet was immersed in the above suspension and shaken for 30 min before being removed; it was irradiated under ultraviolet light at a wavelength of 365 nm for 20 min; it was then ultrasonically cleaned three times alternately with anhydrous ethanol and dichloromethane, and dried in a vacuum oven at 60 °C for 12 h to obtain a superhydrophobic ceramic oil-water separation membrane.

[0060] The microstructure of the superhydrophobic ceramic oil-water separation membrane prepared in this embodiment was tested, and the scanning electron microscope image is shown below. Figure 4 .Depend on Figure 4 It is known that the surface of the superhydrophobic ceramic oil-water separation membrane has a micron / nano composite rough structure, which is beneficial to improving the hydrophobic properties of the ceramic membrane surface.

[0061] Example 5

[0062] This embodiment provides a method for preparing a superhydrophobic ceramic oil-water separation membrane, including the following steps:

[0063] 1) Thiolization modification of mesoporous nano-silica surface: Same as step 1) in Example 1;

[0064] 2) Cleaning of the alumina ceramic sheet surface: Same as step 2) in Example 1;

[0065] 3) Thiolization modification of porous alumina ceramic sheet surface: Same as step 3) in Example 1;

[0066] 4) Superhydrophobic modification of porous alumina ceramic sheet surface: 600 mg of surface-thiolized mesoporous nano-silica, 2 mL of vinyl-terminated polyphenylsiloxane (V-PMDMS), 20 mL of anhydrous tetrahydrofuran and 2 mg of benzoin dimethyl ether (photoinitiator, DMPA) were mixed to obtain a suspension; the surface-thiolized porous alumina ceramic sheet was immersed in the above suspension and shaken for 60 min before being removed; it was irradiated under ultraviolet light at a wavelength of 365 nm for 40 min; it was then ultrasonically cleaned three times alternately with anhydrous ethanol and dichloromethane, and dried in a vacuum oven at 60 °C for 12 h to obtain a superhydrophobic ceramic oil-water separation membrane.

[0067] Example 6

[0068] This embodiment provides a method for preparing a superhydrophobic ceramic oil-water separation membrane, including the following steps:

[0069] 1) Thiolization modification of mesoporous nano-silica surface: Same as step 1) in Example 1;

[0070] 2) Cleaning of the alumina ceramic sheet surface: Same as step 2) in Example 1;

[0071] 3) Thiolization modification of porous alumina ceramic surface: Same as step 3) in Example 1;

[0072] 4) Superhydrophobic modification of porous alumina ceramic surface: 400 mg of surface-thiolized mesoporous nano-silica, 1 mL of methacrylate-terminated dimethylsiloxane (MA-PDMS), 20 mL of anhydrous tetrahydrofuran, and 1 mg of benzoin dimethyl ether (photoinitiator, DMPA) were mixed to obtain a suspension; the surface-thiolized porous alumina ceramic sheet was immersed in the above suspension and shaken for 30 min before being removed; it was irradiated under ultraviolet light at a wavelength of 365 nm for 20 min; it was then ultrasonically cleaned three times alternately with anhydrous ethanol and dichloromethane, and dried in a vacuum oven at 60 °C for 12 h to obtain a superhydrophobic ceramic oil-water separation membrane.

[0073] The microstructure of the superhydrophobic ceramic oil-water separation membrane prepared in this embodiment was tested, and the scanning electron microscope image is shown below. Figure 5 .Depend on Figure 5 It is known that the surface of the superhydrophobic ceramic oil-water separation membrane has a micron / nano composite rough structure, which is beneficial to improving the hydrophobic properties of the ceramic membrane surface.

[0074] Example 7

[0075] This embodiment provides a method for preparing a superhydrophobic ceramic oil-water separation membrane, including the following steps:

[0076] 1) Thiolization modification of mesoporous nano-silica surface: Same as step 1) in Example 1;

[0077] 2) Cleaning of the alumina ceramic sheet surface: Same as step 2) in Example 1;

[0078] 3) Thiolization modification of porous alumina ceramic surface: Same as step 3) in Example 1;

[0079] 4) Superhydrophobic modification of porous alumina ceramic surface: 600 mg of surface-thiolized mesoporous nano-silica, 2 mL of methacrylate-terminated dimethylsiloxane (MA-PDMS), 20 mL of anhydrous tetrahydrofuran solvent, and 2 mg of benzoin dimethyl ether (photoinitiator, DMPA) were mixed to obtain a suspension; the surface-thiolized porous alumina ceramic sheet was immersed in the above suspension and shaken for 30 min before being removed; it was irradiated under ultraviolet light at a wavelength of 365 nm for 40 min; it was then ultrasonically cleaned three times alternately with anhydrous ethanol and dichloromethane, and dried in a vacuum oven at 60 °C for 12 h to obtain a superhydrophobic ceramic oil-water separation membrane.

[0080] Comparative Example 1

[0081] This comparative example provides a method for preparing a modified ceramic membrane, comprising the following steps:

[0082] 1) Thiolization modification of mesoporous nano silica surface: 0.5 g of 3-mercaptopropyltriethoxysilane (thiolization surface modifier, KH590) was dissolved in 100 mL of ethanol, and 0.5 g of mesoporous nano silica (particle size 100 nm) was added to it. The mixture was heated to boiling and refluxed for 5 h. The nanoparticles deposited at the bottom of the centrifuge tube were collected by centrifugation, washed 3 times with ethanol, and dried in a vacuum oven at 100 °C for 12 h to obtain surface-thiolized mesoporous nano silica.

[0083] 2) Cleaning of alumina ceramic sheet surface: Soak the porous alumina ceramic sheet in distilled water and ultrasonically clean it 3 times, then ultrasonically clean it 3 times with anhydrous ethanol, and dry it in a vacuum oven at 100℃ for 12 hours to obtain the cleaned porous alumina ceramic sheet.

[0084] 3) Surface thiolization modification of porous alumina ceramic sheets: 0.5 g of 3-mercaptopropyltriethoxysilane (thiolization surface modifier, KH590) was dissolved in 100 mL of anhydrous ethanol. The cleaned porous alumina ceramic sheets were immersed in the solution and shaken for 5 h. After shaking, the sheets were removed, washed three times with anhydrous ethanol, and dried in a vacuum oven at 100 °C for 5 h to obtain surface thiolized porous alumina ceramic sheets.

[0085] 4) Mix 400 mg of surface-thiolized mesoporous silica nanoparticles, 1 mL of polydimethylsiloxane (PDMS), 20 mL of anhydrous tetrahydrofuran, and 1 mg of benzoin dimethyl ether (photoinitiator, DMPA) to obtain a suspension; immerse the surface-thiolized porous alumina ceramic membrane in the above suspension, shake for 30 min, and then remove it; irradiate it under ultraviolet light at a wavelength of 365 nm for 20 min; clean it three times with alternating ultrasonic cleaning with anhydrous ethanol and dichloromethane, and dry it in a vacuum oven at 60 °C for 12 h to obtain the modified ceramic membrane.

[0086] Comparative Example 2

[0087] This comparative example provides a method for preparing a modified ceramic membrane, comprising the following steps:

[0088] 1) Thiolization modification of mesoporous nano silica surface: 0.5 g of 3-mercaptopropyltriethoxysilane (thiolization surface modifier, KH590) was dissolved in 100 mL of ethanol, and 0.5 g of mesoporous nano silica (particle size 100 nm) was added to it. The mixture was heated to boiling and refluxed for 5 h. The nanoparticles deposited at the bottom of the centrifuge tube were collected by centrifugation, washed 3 times with ethanol, and dried in a vacuum oven at 100 °C for 12 h to obtain surface-thiolized mesoporous nano silica.

[0089] 2) Cleaning of alumina ceramic sheet surface: Soak the porous alumina ceramic sheet in distilled water and ultrasonically clean it 3 times, then ultrasonically clean it 3 times with anhydrous ethanol, and dry it in a vacuum oven at 100℃ for 12 hours to obtain the cleaned porous alumina ceramic sheet.

[0090] 3) Surface thiolization modification of porous alumina ceramic sheets: 0.5 g of 3-mercaptopropyltriethoxysilane (thiolization surface modifier, KH590) was dissolved in 100 mL of anhydrous ethanol. The cleaned porous alumina ceramic sheets were immersed in the solution and shaken for 5 h. After shaking, the sheets were removed, washed three times with anhydrous ethanol, and dried in a vacuum oven at 100 °C for 5 h to obtain surface thiolized porous alumina ceramic sheets.

[0091] 4) Mix 400 mg of surface-thiolized mesoporous silica nanoparticles, 1 mL of vinyl-terminated polydimethylsiloxane (V-PDMS), and 20 mL of anhydrous tetrahydrofuran to obtain a suspension; immerse the surface-thiolized alumina porous ceramic membrane in the above suspension, shake for 30 min, and then remove it; place it in a vacuum oven at 100 °C for 20 min; clean it three times with alternating ultrasonic cleaning with anhydrous ethanol and dichloromethane, and dry it in a vacuum oven at 60 °C for 12 h to obtain the modified ceramic membrane.

[0092] Comparative Example 3

[0093] This comparative example provides a method for preparing a modified ceramic membrane, comprising the following steps:

[0094] 1) Cleaning of alumina ceramic sheet surface: Soak the porous alumina ceramic sheet in distilled water and ultrasonically clean it 3 times, then ultrasonically clean it 3 times with anhydrous ethanol, and dry it in a vacuum oven at 100℃ for 12 hours to obtain the cleaned porous alumina ceramic sheet.

[0095] 2) Surface thiolization modification of porous alumina ceramic sheets: 0.5 g of 3-mercaptopropyltriethoxysilane (thiolization surface modifier, KH590) was dissolved in 100 mL of anhydrous ethanol. The cleaned porous alumina ceramic sheets were immersed in the solution and shaken for 5 h. After shaking, the sheets were removed, washed three times with anhydrous ethanol, and dried in a vacuum oven at 100 °C for 5 h to obtain surface thiolized porous alumina ceramic sheets.

[0096] 3) Mix 1 mL of vinyl-terminated polydimethylsiloxane (V-PDMS), 20 mL of anhydrous tetrahydrofuran, and 1 mg of benzoin dimethyl ether (photoinitiator, DMPA) to obtain a suspension; immerse the surface-thiolized porous alumina ceramic sheet in the above suspension, shake for 30 min, and then remove it; irradiate it under ultraviolet light at a wavelength of 365 nm for 20 min; clean it three times with alternating ultrasonic cleaning with anhydrous ethanol and dichloromethane, and dry it in a vacuum oven at 60 °C for 12 h to obtain a modified ceramic membrane.

[0097] Hydrophobicity test:

[0098] The static water contact angles of the superhydrophobic ceramic oil-water separation membranes prepared in Examples 1-7 and the modified ceramic membranes prepared in Comparative Examples 1-3 were measured at room temperature (25°C) using a DCAT21 contact angle meter (Dataphysics, Germany). The test results are shown in Table 1.

[0099] Table 1

[0100] Serial Number Water contact angle Example 1 155.9° Example 2 146.3° Example 3 149.1° Example 4 152.3° Example 5 153.9° Example 6 149.3° Example 7 154.3° Comparative Example 1 89.3° Comparative Example 2 97.2° Comparative Example 3 136.2°

[0101] As shown in Table 1, the water contact angles of Examples 1-7 are 146.3°–155.9°, while those of Comparative Examples 1-3 are 89.3°–136.2°. Examples 1-7 exhibit larger water contact angles and better hydrophobic properties, demonstrating superhydrophobicity. Examples 1-7 utilize alkenyl-terminated polysiloxanes, under the influence of ultraviolet light and a photoinitiator, to undergo a mercapto-alkene click chemical reaction with mercapto groups on the surface of mesoporous silica and porous alumina ceramic sheets, forming carbon-sulfur bonds. This allows the alkenyl-terminated polysiloxanes to be firmly covalently bonded to the surfaces of mesoporous silica and porous alumina ceramic sheets, and to firmly modify the mesoporous silica onto the surface of the porous alumina ceramic sheets, achieving chemical bonding and superhydrophobic modification of the ceramic sheet surface, resulting in a superhydrophobic ceramic oil-water separation membrane.

[0102] Oil-water separation efficiency test:

[0103] The oil-water separation efficiency of the superhydrophobic ceramic oil-water separation membranes prepared in Examples 1-7 and the modified ceramic membrane obtained in Comparative Example 3 (which has the optimal water contact angle) was tested. The results are shown in Table 2. The specific test method for oil-water separation efficiency is as follows:

[0104] A superhydrophobic ceramic oil-water separation membrane was placed in a vacuum filter. 30 mL of chloroform and 30 mL of water were mixed to obtain an oil-water mixture. This mixture was then poured into the vacuum filter for oil-water separation. The oil phase passed through the hydrophobic ceramic oil-water separation membrane and flowed into the lower filter cup, while the aqueous phase was retained above the membrane. After separation, the masses of the separated oil and aqueous phases were weighed. Then, the oil-water separation efficiency was calculated using the formula:

[0105] Oil-water separation efficiency (%) = m1 / m × 100%

[0106] Where m1 is the mass of the oil phase obtained after separation; m is the initial mass of the oil in the oil-water mixture.

[0107] Table 2

[0108] Serial Number Oil-water separation efficiency Example 1 99.3% Example 2 98.3% Example 3 98.5% Example 4 98.7% Example 5 98.9% Example 6 98.5% Example 7 99.0% Comparative Example 3 93.2%

[0109] As shown in Table 2, the oil-water separation efficiency of Examples 1-7 is 98.3% to 99.3%, while that of Comparative Example 3 is 93.2%. Examples 1-7 have higher oil-water separation efficiency.

[0110] Chemical stability and thermal stability tests:

[0111] The superhydrophobic ceramic oil-water separation membranes prepared in Examples 1, 4 and 6 and the modified ceramic membranes prepared in Comparative Examples 1-3 were heated at 200°C for 12 hours. The static water contact angle was measured at room temperature (25°C) using a DCAT21 contact angle measuring instrument (Dataphysics, Germany). The results are shown in Table 3.

[0112] The superhydrophobic ceramic oil-water separation membranes prepared in Examples 1, 4 and 6 and the modified ceramic membranes prepared in Comparative Examples 1-3 were soaked in hydrochloric acid solution with pH=1 for 72 h, washed three times with deionized water and ethanol respectively, and dried in an oven at 70°C for 6 h. The static water contact angle was measured at room temperature (25°C) using a DCAT21 contact angle meter (Dataphysics, Germany). The results are shown in Table 3.

[0113] The superhydrophobic ceramic oil-water separation membranes prepared in Examples 1, 4, and 6, and the modified ceramic membranes prepared in Comparative Examples 1-3 were soaked in sodium hydroxide solution at pH=14 for 72 h, washed three times with deionized water and ethanol respectively, and dried in an oven at 70°C for 6 h. The static water contact angle was measured at room temperature (25°C) using a DCAT21 contact angle meter (Dataphysics, Germany). The results are shown in Table 3.

[0114] Table 3

[0115]

[0116] As shown in Tables 1 and 3, after heating at 200°C for 12 hours, the water contact angle of Example 1 decreased from 155.9° to 154.3°, a decrease of 1.6°; the water contact angle of Example 4 decreased from 152.3° to 151.0°, a decrease of 1.3°; and the water contact angle of Example 6 decreased from 149.3° to 149.1°, a decrease of 0.2°. The decrease in water contact angle for Examples 1, 4, and 6 ranged from 0.2° to 1.6°. After heating at 200°C for 12 hours, the water contact angle of Comparative Example 1 decreased from 89.3° to 86.3°, a decrease of 3°; the water contact angle of Comparative Example 2 decreased from 97.2° to 93.2°, a decrease of 4°; and the water contact angle of Comparative Example 3 decreased from 136.2° to 133.2°, a decrease of 3°. The decrease in water contact angle for Comparative Examples 1-3 ranged from 3° to 4°. The comparison shows that the water contact angle of Examples 1, 4 and 6 changed less after heating at 200°C for 12 hours, indicating that they have better thermal stability.

[0117] As shown in Tables 1 and 3, after soaking in hydrochloric acid solution at pH=1 for 72 hours, the water contact angle of Example 1 decreased from 155.9° to 153.9°, a decrease of 2°; the water contact angle of Example 4 decreased from 152.3° to 151.5°, a decrease of 0.8°; and the water contact angle of Example 6 decreased from 149.3° to 148.2°, a decrease of 1.1°. After soaking in sodium hydroxide solution at pH=14 for 72 hours, the water contact angle of Example 1 decreased from 155.9° to 154.0°, a decrease of 1.9°; the water contact angle of Example 4 remained unchanged; and the water contact angle of Example 6 decreased from 149.3° to 148.7°, a decrease of 0.6°. In summary, the decrease in water contact angle of Examples 1, 4, and 6 after soaking in hydrochloric acid solution or sodium hydroxide solution ranged from 0 to 2°.

[0118] As shown in Tables 1 and 3, after soaking in hydrochloric acid solution with pH=1 for 72 hours, the water contact angle of Comparative Example 1 decreased from 89.3° to 82.3°, a decrease of 7°; the water contact angle of Comparative Example 2 decreased from 97.2° to 92.1°, a decrease of 5.1°; and the water contact angle of Comparative Example 3 decreased from 136.2° to 129.4°, a decrease of 6.8°. After soaking in sodium hydroxide solution with pH=14 for 72 hours, the water contact angle of Comparative Example 1 decreased from 89.3° to 81.9°, a decrease of 7.4°; the water contact angle of Comparative Example 2 decreased from 97.2° to 91.8°, a decrease of 5.4°; and the water contact angle of Comparative Example 3 decreased from 136.2° to 130.5°, a decrease of 5.7°. In summary, the water contact angle of Comparative Examples 1-3 decreased by 5.1° to 7.4° after immersion in hydrochloric acid solution or sodium hydroxide solution.

[0119] The comparison shows that the water contact angles of Examples 1, 4, and 6 changed less after immersion in hydrochloric acid or sodium hydroxide solutions, indicating better chemical stability.

[0120] As can be seen from the above examples and comparative examples, the method for preparing superhydrophobic ceramic oil-water separation membranes in Examples 1-7 involves an alkenyl-terminated polysiloxane reacting with surface-thiolized porous alumina ceramic sheets and surface-thiolized mesoporous nano-silica under ultraviolet light irradiation and photoinitiator action, resulting in a thiol-alkene click chemical reaction. This firmly fixes the alkenyl-terminated polysiloxane onto the surface of the mesoporous nano-silica and the porous alumina ceramic sheets, and firmly modifies the surface of the porous alumina ceramic sheets with the mesoporous nano-silica, thus obtaining a superhydrophobic ceramic oil-water separation membrane. The prepared superhydrophobic ceramic oil-water separation membrane possesses superhydrophobic properties as well as excellent oil-water separation efficiency, chemical stability, and thermal stability.

[0121] The methods for preparing superhydrophobic ceramic oil-water separation membranes in Examples 1-7 can be summarized as follows:

[0122] (1) Mix alkenyl-terminated polysiloxane, surface-thiolized mesoporous nano silica, photoinitiator and tetrahydrofuran to obtain a suspension;

[0123] The ratio of the volume of the alkenyl-terminated polysiloxane, the mass of the surface-thiolized mesoporous nano-silica, and the mass of the photoinitiator is 1 mL:(300-400) mg:1 mg.

[0124] (2) Immerse the surface-thiolized porous alumina ceramic sheet in the above suspension, shake, take it out, irradiate with ultraviolet light; wash, dry, and obtain a superhydrophobic ceramic oil-water separation membrane.

[0125] In the above method, the alkenyl-terminated polysiloxane is one of vinyl-terminated polydimethylsiloxane, vinyl-terminated polyphenylsiloxane, and methacrylate-terminated dimethylsiloxane, or any combination thereof;

[0126] The photoinitiator is benzoin dimethyl ether.

[0127] In step (1), the volume ratio of the alkenyl-terminated polysiloxane to the tetrahydrofuran is (1-2):20.

[0128] In step (2), the oscillation time is 30-60 min and the ultraviolet light irradiation time is 20-40 min.

[0129] In the above method, the preparation method of the surface-thiolized mesoporous nano-silica is as follows:

[0130] Mesoporous nano-silica was dispersed in an ethanol solution of a mercapto-modified surface modifier and refluxed at boiling for 5–12 h; then centrifuged, washed, and dried to obtain surface-mercapto-modified mesoporous nano-silica.

[0131] Wherein, the concentration of the thiolated surface modifier in the ethanol solution of the thiolated surface modifier is 5-10 mg / mL, and the thiolated surface modifier is 3-mercaptopropyltriethoxysilane;

[0132] The mass ratio of the mesoporous nano-silica to the mercaptoized surface modifier is 1:(1-1.2).

[0133] In the above method, the preparation method of the surface-thiolized porous alumina ceramic sheet is as follows:

[0134] Alumina porous ceramic sheets were immersed in an ethanol solution of a mercapto-modified surface modifier, shaken for 5–12 hours, and then removed; washed and dried to obtain surface-mercapto-modified alumina porous ceramic sheets.

[0135] The concentration of the thiolated surface modifier in the ethanol solution of the thiolated surface modifier is 5-10 mg / mL, and the thiolated surface modifier is 3-mercaptopropyltriethoxysilane.

Claims

1. A method for preparing a superhydrophobic ceramic oil-water separation membrane, characterized in that, Includes the following steps: (1) Mix alkenyl-terminated polysiloxane, surface-thiolized mesoporous nano silica, photoinitiator and tetrahydrofuran to obtain a suspension; The ratio of the volume of the alkenyl-terminated polysiloxane, the mass of the surface-thiolized mesoporous nano-silica, and the mass of the photoinitiator is 1 mL:(300-400) mg:1 mg. (2) Immerse the surface-thiolized porous alumina ceramic sheet in the above suspension, shake, take it out, irradiate with ultraviolet light; wash, dry, and obtain a superhydrophobic ceramic oil-water separation membrane.

2. The method according to claim 1, characterized in that, The alkenyl-terminated polysiloxane is one of vinyl-terminated polydimethylsiloxane, vinyl-terminated polyphenylsiloxane, and methacrylate-terminated dimethylsiloxane, or any combination thereof.

3. The method according to claim 1, characterized in that, The photoinitiator is benzoin dimethyl ether.

4. The method according to claim 1, characterized in that, In step (1), the volume ratio of the alkenyl-terminated polysiloxane to the tetrahydrofuran is (1-2):

20.

5. The method according to claim 1, characterized in that, In step (2), the oscillation time is 30-60 min and the ultraviolet light irradiation time is 20-40 min.

6. The method according to claim 1, characterized in that, The method for preparing the surface-thiolized mesoporous nano-silica is as follows: Mesoporous nano-silica was dispersed in an ethanol solution of a mercapto-modified surface modifier and refluxed at boiling for 5–12 h. Centrifugation, washing, and drying yielded surface-thiolized mesoporous nano-silica. The concentration of the thiolated surface modifier in the ethanol solution of the thiolated surface modifier is 5-10 mg / mL, and the thiolated surface modifier is 3-mercaptopropyltriethoxysilane.

7. The method according to claim 6, characterized in that, The mass ratio of the mesoporous nano-silica to the mercaptoized surface modifier is 1:(1-1.2).

8. The method according to claim 1, characterized in that, The method for preparing the surface-thiolized porous alumina ceramic sheet is as follows: The porous alumina ceramic sheet was immersed in an ethanol solution of a mercapto-modified surface modifier and shaken for 5–12 hours before being removed. Wash and dry to obtain porous alumina ceramic sheets with surface thiolized alumina; The concentration of the thiolated surface modifier in the ethanol solution of the thiolated surface modifier is 5-10 mg / mL, and the thiolated surface modifier is 3-mercaptopropyltriethoxysilane.

9. A superhydrophobic ceramic oil-water separation membrane, characterized in that, The superhydrophobic ceramic oil-water separation membrane is the superhydrophobic ceramic oil-water separation membrane prepared by any of the methods described in claims 1-8.

10. The application of superhydrophobic ceramic oil-water separation membrane in oil-water separation, characterized in that, The superhydrophobic ceramic oil-water separation membrane is the superhydrophobic ceramic oil-water separation membrane as described in claim 9.

Citation Information

Patent Citations

  • Method for preparing tubular ceramic membrane for oil-water separation

    CN103521095A

  • Aluminum oxide ceramic composite membrane for oil-water separation and preparation method thereof

    CN106975369A

  • Preparation and application of high-stability underwater super-oleophobic silicon carbide ceramic membrane

    CN117865719A